Bioindicators of water quality with different riparian cover in the Guapara micro watershed, Ecuador - Urdánigo , Juan; Pérez, Karla; Intriago, Elian; Arriaga, Gabriela; Zambrano, Solange; Prieto, Oscar (Revista de la Facultad de Agronomía de la Universidad del Zulia, 2022)
Agricultural activities produce changes in the margins of the stream banks, causing disturbances in water quality, and in the assemblage of aquatic insect communities. The objective of this research is to evaluate the changes in the structure and composition of the aquatic macroinvertebrate community, and physicochemical variables in relation to the land use of the Guapara river, Cotopaxi province, Ecuador. Samplings were conducted during the rainy season (December to February 2018-2019) in three streams with different riparian cover: agricultural, native forest, and forest plantations, where samples of aquatic insects and physicochemical parameters were collected in situ. A total of 461 aquatic insects corresponding to 7 orders and 25 families were collected. In general, the highest abundance in order and family was presented by Ephemeroptera with 34 %, and Leptophlebiidae with 21 % respectively. According to the Ephemeroptera, Plecoptera Trichoptera (EPT) index, the highest ecological condition was found in streams with native forest cover, and forest plantations respectively, and decreased in the stream with agricultural cover; while BMWP-Cr indicated water contamination in the three streams. Hydrobiosidae (Trichoptera) were associated with high turbidity values; while Gerridae (Hemiptera) were associated with high dissolved oxygen concentrations; in addition, Ptilodactylidae (Coleoptera) preferred the Q1-CA, and Q3-CF conditions, while Leptophlebiidae (Ephemeroptera) were associated with the stream of native forest. A negative influence of agricultural activity on the physicochemical parameters of the water and on the structure of the aquatic insect community assemblage was evidenced.